THE LEGAL ASPECTS OF FERTILITY IN A PRACTICAL GYNECOLOGICAL ONC - N. Yu. Chernus '; A. G. Kedrova; E. V. Babayants; V. E. Voytsitskiy; S. E. Krasil'nikov (ABV-press, 2018)
Annually in Russia about 30 000 cases of oncological diseases in young women are diagnosed. The diagnosis of reproductive problems associated with treatment is still little discussed, although the practical recommendations of many professional organizations, including the American Society of Clinical Oncology, underscore the need for mandatory oncologist review of options for maintaining the patient's fertility. The article analyzes the medical organization when detected in a female patient of childbearing age cancer is to use therapies aimed at subsequent implementation by the patient of her reproductive rights. It is noted that such opportunities are limited to current law, giving the right to persons with cancer at the expense of budget funds to use the methods of assisted reproduction and cryoconservation technologies for maintaining reproductive potential in cancer patients. The article presents evidence of the urgency of introducing changes to the orders of the Ministry of Health of Russia that limit the use of methods of assisted reproductive technologies for cancer patients at the expense of the budget.